Fabrication of highly transparent thulium-doped Al2O3 nanocrystalline ceramics with broadband emission at 1.8 μm - Wu, Xingzhong; Kodera, Yasuhiro; Garay, Javier E. (Optical materials, 2022)
Rare earth (RE) doped polycrystalline Al2O3 ceramics have attracted increasing research interest in the past decade for lasing and lighting applications because of their outstanding thermal conductivity and fracture strength enabling power scaling. However, the optically anisotropic nature of Al2O3 causes birefringent scattering in polycrystals, limiting the in-line transparency across visible and NIR wavelength range. To improve the transparency of Al2O3 ceramics, great control over powder processing and densification techniques are required to optimize its nanostructure. In this work, we present the first report of thulium incorporated nanocrystalline Al2O3 ceramic. The Tm:Al2O3 ceramic presented has the highest transparency among RE:Al2O3 reported to date, with a total loss coefficient of 0.6 cm−1 at the major emission wavelength 1.78 μm. •Highly transparent Tm doped alumina ceramics with were fabricated.•Modeling results agree well with measured transmission.•The ceramics have fine grain sizes leading to low loss coefficient.•The ceramics have broadband emission around 1.8 μm, interesting for laser applications.